The Influence of Price, Location and Service Quality on Purchasing Decision at Fried Chicken & Ayam Geprek Wong Nganjuk - Erliana Putri, Puspitasari; Kurniawan, Rony (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This reserach aims to determine  the influence of price, location, and service quality on consumer decisions to purchase Fried Chicken & Ayam Geprek Wong Nganjuk products. Design / Method / Approach : This research applies a quantitative method with a focus on causality. The population analyzed is all customers who come to Fried Chicken & Ayam Geprek Wong Nganjuk whose number is unlimited. From this population, this study took a sample of 40 respondents through a random sampling technique (accidental sampling). Data were gathered through the use of a questionnaire. To analyze the data, this study applied the classical assumption test, multiple linear regression, determination coefficient test, and hypothesis testing using SPSSv23. Research Finding : The findings of research statement states that price, place, and service quality have a significant positive influence on purchasing choices at Fried Chicken & Ayam Geprek Wong Nganjuk. Theoretical contribution / Originality : This research focuses on an in-depth understanding of how price, location and service quality together influence consumers' influence how consumers make purchasing decisions. This study investigates the complex relationships between these three variables to shape consumer preferences and influence their purchasing decision. Practitionel / Policy implication : This study has practical implications for Fried Chicken & Ayam Geprek Wong Nganjuk in encouraging increased purchasing decisions. Research limitation : This research has limitations that may influence  the results and generalization of research at Fried Chicken & Ayam Geprek Wong Nganjuk is that this research only focuses on the Fried Chicken & Ayam Geprek Wong Nganjuk business, so the results obtained do not necessarily reflect conditions in similar businesses in other areas